Bioenergetic studies in the parasitic protist Trypanosoma brucei: functional characterisation of the mitochondrial FoF1-ATP synthase/ATPase complex - Hierro Yap, Carolina (Jihočeská univerzita, 2021)
This Ph.D. thesis focuses on the functional characterisation of the mitochondrial FoF1-ATP synthase/ATPase complex in the parasitic protist Trypanosoma brucei, a eukaryotic system that enables the study of both operation modes of the complex in physiological settings. The results presented in this thesis are divided in four topics: (i) bioenergetics consequences of mitochondrial FoF1-ATP synthase deficiency in two life cycle stages of the parasite, with emphasis on the roles of subunits ATPaseTb1 and OSCP, (ii) changes in energy metabolism of bloodstream form parasites depleted of cardiolipin, (iii) role of the FoF1-ATP synthase dimerisation in mitochondrial biogenesis and bioenergetics, with focus on the functional characterisation of the dimer-specific subunit g in the insect stage of the parasite, and (iv) role of subunit OSCP in the structural and functional integrity of the FoF1-ATPase in trypanosomes lacking mitochondrial DNA (akinetoplastic).
Bioenergetic studies in the parasitic protist Trypanosoma brucei: functional characterisation of the mitochondrial FoF1-ATP synthase/ATPase complex
Keywords: Trypanosoma brucei; mitochondria; FoF1-ATP synthase/ATPase; bioenergetics.; Trypanosoma brucei; mitochondria; FoF1-ATP synthase/ATPase; bioenergetics.